Direct and indirect effects of measures and reasons morphometric on the body yield of Nile tilapia, Oreochromis niloticus - doi: 10.4025/actascianimsci.v35i4.19807 - Carlos Cicinato Vieira Melo; Rafael Vilhena Reis Neto; Adriano Carvalho Costa; Rilke Tadeu Fonseca de Freitas; Thiago Archangelo Freato; U. N. Souza (2013)
The study was carried out with the objective of verifying which measures and morphometric ratios are more directly related to the body yield of Nile tilapia, Oreochromis niloticus, in two weight classes. Data were analyzed from 257 specimens of tilapia divided into two weight classes: p1 = 400 to 599 g and p2 = 600 to 900 g. The morphometric measurements standard length (SL), head length (HL), body height (BH) and body width (BW), and the ratios of these measures (HL / SL, BH / SL, BW / SL, HL / BH, BW / BH, BW / HL) were evaluated. The following body yields were calculated: carcass (RCAR), fillet (RFILE) and head (RCAB). The data were initially submitted to the "stepwise" procedure to eliminate problems of multicollinearity among the morphometric variables, then the correlations between the dependent variables (body yield) and the independent variables (measured and morphometric relationships) were calculated. Later, these correlations were divided into direct and indirect effects through path analysis, and the direct and indirect contributions of each variable measured in percentage terms. The morphometric ratio BW/HL, for both weight classes, was the variable most highly correlated and with the highest direct effect on RFILE and RCAB, showing to be the most important morphometric variable studied for tilapia carcass trait determination.